2011
DOI: 10.4061/2011/270624
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Hypertension: The Regulatory Role of Leptin

Abstract: Leptin is a 16-kDa-peptide hormone that is primarily synthesized and secreted by adipose tissue. One of the major actions of this hormone is the control of energy balance by binding to receptors in the hypothalamus, leading to reduction in food intake and elevation in temperature and energy expenditure. In addition, increasing evidence suggests that leptin, through both direct and indirect mechanisms, may play an important role in cardiovascular and renal regulation. While the relevance of endogenous leptin ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 96 publications
2
23
0
2
Order By: Relevance
“…It is important than women control body mass gain because an excess can result in hypertension [7]. The impact of obesity in the etiopathogenesis of arterial hypertension is undeniable [8]. Both obesity and arterial hypertension in pregnant women are known to lead to uteroplacental blood flow impairment [9], resulting in changes in placenta morphology, ultimately decreasing the active surface of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…It is important than women control body mass gain because an excess can result in hypertension [7]. The impact of obesity in the etiopathogenesis of arterial hypertension is undeniable [8]. Both obesity and arterial hypertension in pregnant women are known to lead to uteroplacental blood flow impairment [9], resulting in changes in placenta morphology, ultimately decreasing the active surface of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin causes myocardial hypertrophy and water and salt retention and is associated with diabetes and hypertension, conditions that contribute to high morbidity and mortality rates, particularly in end stage kidney disease [31] . Finally, leptin and insulin not only present similar metabolic and hemodynamic actions, but also display the same patterns of distribution with respect to BMI in HD [30,32] . We investigated cardiac and metabolic biomarkers in HD subjects with respect to urinary output, and propose another potential protective cardiovascular mechanism high BMI individuals display in HD.…”
Section: Introductionmentioning
confidence: 96%
“…While some studies have shown leptin presents natriuretic effects, many others have reported its association with water and salt retention, sympathetic nervous system activation and hypertension, which could add to insulin hemodynamic effects [32,48] . With respect to the cardiovascular system, leptin (as insulin) is involved in the pathogenesis of myocyte hypertrophy [32,48] . Finally, the obesity paradox in hemodialysis has always been related to an elevated weight and assumed to be due to fat.…”
mentioning
confidence: 99%
“…Leptin is a 16 kDa-peptide (167 amino acids) that is synthesized and secreted predominantly by white adipose tissue (1). One of the major effects of this hormone is the control of energy balance via the hypothalamus, which was previously considered to be mediated through binding to leptin receptors in the hypothalamus (24).…”
Section: Introductionmentioning
confidence: 99%